Project-Based Learning Supports Students' Creative Thinking in Science Education - Ramdhani Sucilestari; Agus Ramdani; AA Sukarso; Susilawati Susilawati; Joni Rokhmat (Jurnal Penelitian Pendidikan IPA, 2023)
Creativity is recognized as a crucial 21st-century skill. Creativity plays a significant role in societal life, bringing forth something that did not exist before, whether it be in the form of products, processes, or ideas. Creativity is vital for navigating the limitations we encounter, solving problems across various aspects of life, and generating new opportunities or works to address a range of issues, including in the realm of education. Creative thinking is the process that yields creativity. The better someone is at creative thinking, the more creative they are as individuals. In other words, that person possesses high creativity. Involving students in designing their own experimental procedures will encourage their scientific creativity. Project-based learning requires students to conduct experiments to solve problems and complete given projects. Creative thinking from students is essential in these project endeavors. Hence, in this article, the researchers attempt to unearth the advantages inherent in project-based learning for bolstering students' creative thinking skills in science education